Pelatihan Online Pembuatan Totebag Menggunakan Kresek Bekas dan Kain Perca - Dias Ayu Budi Utami (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Currently, social media is widely used for negative activities or things, for example fraud and account break-ins. Many activities are carried out online, for example: school and work which is known as work from home. So all activities are more focused on gadgets. To maximize time productively, it is necessary to hold activities that hone skills. In addition to filling time, these skills can be used to create works that are marketable so that they can increase income. The implementation of online training with knitting activities to make handicrafts such as totebags is expected to be able to help the community, especially members of the LINE Learning Knitting and Sewing Group, to make more use of social media and to be more productive in their time. The activity was carried out in the LINE group to learn knitting and sewing. In order to reduce the existing problems, namely helping the community in using social media wisely and spending their free time productively when PPKM is in progress by adding knitting skills which can be sold so that they can increase their income and reduce plastic waste by using totebags for shopping bags. and utilizing crackle waste, cloth into a masterpiece.